Role of TSHs and FT4 Levels in Thyroid Nodule Histopathology - Novitasari; Anak Agung Ayu Ngurah Susraini; Kadek Agus Suhardinata (Universitas Muhammadiyah Malang, 2026)
Thyroid nodules are a common clinical finding, although only a minority are malignant. Thyroid stimulating hormone (TSH) and free thyroxine (FT4) have been investigated as potential biomarkers for predicting thyroid malignancy, yet previous studies have shown inconsistent results. This study aimed to analyse the association between TSHs and FT4 levels and histopathological outcomes in patients with thyroid nodules undergoing surgery. This analytical observational study used a cross-sectional design with retrospective medical record data from patients who underwent thyroid surgery at Wangaya Regional General Hospital during 2021–2025. Total sampling was applied based on the inclusion criteria, resulting in 121 patients with complete histopathological, TSHs, and FT4 data. The association between histopathological findings and hormone levels was analysed using chi-square test and logistic regression. Most patients were female (84.3%), and benign lesions predominated (71.1%). Higher TSHs levels were more frequent in borderline (66.7%) and malignant (56.3%) groups than in benign lesions (46.5%), but the association was not statistically significant (p=0.535). Lower FT4 levels were also more common in borderline (66.7%) and malignant groups (62.5%) than in benign lesions (48.8%), without significant association (p=0.367). TSHs and FT4 levels were not significantly associated with histopathological outcomes in patients undergoing thyroid surgery. These parameters should not be used as single predictors of thyroid malignancy.